2003
DOI: 10.4161/cbt.2.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Mitoxantrone Mediates Demethylation and Re-Expression of Cyclin D2, Estrogen Receptor 14.3.3 Sigma In Breast Cancer Cells

Abstract: In addition to its action as a topoisomerase II poison, mitoxantrone is activated by formaldehyde to bind DNA, forming DNA-adducts specifically at 5'CpG and CpA sequences, with an enhancement of adducts at methylated CpG sites. The butyric acid prodrug, AN-9 (pivaloyloxymethyl butyrate), releases formaldehyde upon cellular hydrolysis and our previous studies have shown that mitoxantrone acts synergistically with AN-9 in cytotoxicity assays. In this paper, we investigated the impact of methylation levels in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Both agents induce global and localized CpG island-demethylation and re-expression of the associated genes in a cellular environment (55,57) and these effects may contribute towards their growth inhibitory properties. Similarly, formaldehyde-activated mitoxantrone, a close structural analogue of pixantrone, can also mediate localized demethylation of CpG islands in several cancer-associated genes (58). A functional consequence of this demethylation was the reactivation of the associated gene.…”
Section: Discussionmentioning
confidence: 99%
“…Both agents induce global and localized CpG island-demethylation and re-expression of the associated genes in a cellular environment (55,57) and these effects may contribute towards their growth inhibitory properties. Similarly, formaldehyde-activated mitoxantrone, a close structural analogue of pixantrone, can also mediate localized demethylation of CpG islands in several cancer-associated genes (58). A functional consequence of this demethylation was the reactivation of the associated gene.…”
Section: Discussionmentioning
confidence: 99%
“…19; summarized in Table II). To establish how cytosine methylation caused such a dramatic enhancement of adduct formation together with a corresponding increase of biological activity (19,20) we determined the relative free energy of binding of mitoxantrone to each se- quence (with intercalation of the drug chromophore between the C and G residues) with the drug intercalated in either the major or minor groove, and these energies are summarized in Table II. Binding via the major groove was much more favorable than the minor groove for the non-methylated sequence, and this is consistent with previous NMR studies which revealed that the drug side chains were located in the major groove (29).…”
Section: Fig 4 Effect Of Guanine Modifications On Mitoxantrone-dna mentioning
confidence: 99%
“…Recently, we have shown that in tumor cells in culture the activity of mitoxantrone depends on the methylation status of the cell (20). Mitoxantrone-DNA adduct levels decreased when breast cancer cells were pretreated with the DNA de-methylating agent 5-aza-2-deoxycytidine, 1 and DK08 cells in which the DNA methyltransferase activity had been knocked out (resulting in a 50% decrease of methylation levels compared with the parental HCT116 cells) were also less sensitive to mitoxantrone (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since hypermethylated genes may be involved in the etiology of the disease and may be early events in neoplastic progression, these genes make attractive targets for therapeutics and disease detection/monitoring (Bovenzi et al, 1999;Evron et al, 2001a;Umbricht et al, 2001;Muller et al, 2003;Oshiro et al, 2003;Parker et al, 2003). Agents that reactivate gene expression silenced by methylation have favorable therapeutic indices and are now entering clinical trials for a variety of cancers (Baylin, 2004;Dowell and Minna, 2004;Egger et al, 2004;Zelent et al, 2004).…”
Section: Introductionmentioning
confidence: 99%